Trust, Technology Awareness and Satisfaction Effect into the Intention to Use Cryptocurrency among Generation Z in Malaysia - Alaeddin, Omar; Altounjy, Rana (International Journal of Engineering and Technology, 2018)
Due to the current inclination of central bank of Malaysia to regulate the usage of digital currencies in early 2018, this paper investigates the factors affecting Malaysian Generation Z attitude and intention to use cryptocurrency in their financial decisions. Quantitative method has been applied and a sample of 230 final year students of Universiti Kuala Lumpur business school has been used. The investigation detected a significant impact of the awareness and trust into the attitude -which in support of the satisfaction with cryptocurrency service- can create an intention to use cryptocurrency.